2020
DOI: 10.3389/fmicb.2020.01269
|View full text |Cite
|
Sign up to set email alerts
|

Conserved G-Quadruplex Motifs in Gene Promoter Region Reveals a Novel Therapeutic Approach to Target Multi-Drug Resistance Klebsiella pneumoniae

Abstract: An opportunistic pathogen, Klebsiella pneumoniae is known to cause life-threating nosocomial infection with a high rate of morbidity and mortality. Evolutions of multi-drug-resistant and hyper-virulent strains of K. pneumoniae make the situation worse. Currently, there is no incisive drug molecule available for drug-resistant hyper-virulent K. pneumoniae infection that emphasizes the need for identification of novel and more promising drug ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 52 publications
1
24
0
Order By: Relevance
“…Pyridostatin is also observed to stabilize the G-quadruplex structure formed in the mRNA of the nuclear antigen 1 protein of EBV, leading to its translation suppression [ 39 ]. Recently, BRACO-19 has shown an inhibitory effect on Mycobacterium tuberculosis, and Klebsiella pneumoniae, while Quarfloxin inhibited Plasmodium falciparum, by stabilizing G-quadruplexes present in various regions of their genome [ 25 , 40 , 41 ]. Previously, 9-Aminoacridine and its derivatives have been observed for their anti-proliferative properties in cancer cells [ 42 ] by binding to the telomeric region [ 43 ], the c-Myc gene [ 44 ] and c-Kit promoter [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…Pyridostatin is also observed to stabilize the G-quadruplex structure formed in the mRNA of the nuclear antigen 1 protein of EBV, leading to its translation suppression [ 39 ]. Recently, BRACO-19 has shown an inhibitory effect on Mycobacterium tuberculosis, and Klebsiella pneumoniae, while Quarfloxin inhibited Plasmodium falciparum, by stabilizing G-quadruplexes present in various regions of their genome [ 25 , 40 , 41 ]. Previously, 9-Aminoacridine and its derivatives have been observed for their anti-proliferative properties in cancer cells [ 42 ] by binding to the telomeric region [ 43 ], the c-Myc gene [ 44 ] and c-Kit promoter [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…G-quadruplex motifs, depending upon its location, regulates the expression of the genes. PGQ motifs at the upstream/promoter region of the gene are reported to regulate the transcription of the harboring genes and are widely used as therapeutic targets against various pathogenic viruses, bacteria, protozoa, and other human diseases including cancer and neurological disorders (Balasubramanian et al, 2011;Kota et al, 2015;Tosoni et al, 2015;Perrone et al, 2017a;Shankar et al, 2020). Stabilization of PGQ motifs in the open reading frame of a gene has been reported to suppress their expression (Endoh et al, 2013b).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, three highly conserved GQ forming motifs were recognized in the hsdS, recD, and pmrA genes which could act as potential drug targets against pathogenic Streptococcus pneumoniae (Mishra et al, 2019a). A recent analysis revealed the presence of GQ motifs in various genes of Klebsiella pneumoniae that influenced the gene expression (Shankar et al, 2020). Likewise, several human infecting viruses including Zika (Fleming et al, 2016), Nipah (Majee et al, 2020a), Herpes Simplex virus (Biswas et al, 2016), Human Papillomavirus (Tlučková et al, 2013), and Human Adenovirus (Majee et al, 2020b) are reported to possess potential GQ forming sequences.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the presence of potential G quadruplex sequences has been mapped to promoter regions of Mycobacterium tuberculosis [55] and direct regulation of transcription due to G-quadruplex stabilization was shown in the soil bacterium Paracoccus denitrificans [56]. Furthermore, G-quadruplexes in promoter regions have been suggested as a novel therapeutic approach for multidrug-resistant Klebsiella pneumoniae [57].…”
Section: Promoter Structure Motifsmentioning
confidence: 99%